2020
DOI: 10.15376/biores.15.4.9656-9671
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antimicrobial activity of extracts from thyme and rosemary against Staphylococcus aureus and Candida albicans

Abstract: Different concentrations of ethanolic extracts of thyme (Zataria multiflora) and rosemary (Rosmarinus officinalis) were evaluated to determine their antimicrobial activity using the agar-well diffusion method. The values of inhibition zone diameter (IZD) for Candida albicans fungus and Staphylococcus aureus Gram-positive bacteria were determined. The bioactivities of two various extracts were studied, and the chemical composition of the extracts were identified using gas chromatography-mass spectrometry (GC-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…According to Saleem et al [45], carvacrol and thymol are the two primary constituents of fresh and dried plants, respectively. Carvacrol (52.32%), linalool L (15.96%), thymol (9.59%), 1-methylpyrroline (3.53%), and trans-caryophyllene (3.43%) were the major constituents of thyme (Zataria multiflora) extract [46]. Mehrabi et al [47] reported that the main components in thyme were thymol (25.30%), δ-2-carene (8.825%), and carvacrol (8.43%).…”
Section: Chemical Composition Of Cfs From S Thermophilusmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Saleem et al [45], carvacrol and thymol are the two primary constituents of fresh and dried plants, respectively. Carvacrol (52.32%), linalool L (15.96%), thymol (9.59%), 1-methylpyrroline (3.53%), and trans-caryophyllene (3.43%) were the major constituents of thyme (Zataria multiflora) extract [46]. Mehrabi et al [47] reported that the main components in thyme were thymol (25.30%), δ-2-carene (8.825%), and carvacrol (8.43%).…”
Section: Chemical Composition Of Cfs From S Thermophilusmentioning
confidence: 99%
“…)-(4.54%), (Z, Z)-6, 9-Cis-3, 4-epoxy-nonadecadiene (3.60%), carvacrol (3.59%), cryptomeridiol (3.22%), heptadecanoic acid, ethyl ester (2.03%), and naphthalene, decahydro-(1.28%) [52]. Various factors, such as geographical conditions, cultural differences, plant development stage, drying methods, and extraction methods, affect the qualitative and quantitative properties of bioactive components in a plant [46,47,53]. These variables are the cause of the detection of various components in thyme extract.…”
Section: Chemical Composition Of Cfs From S Thermophilusmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second step, approximately 50, 50, and 40 g from pieces of fruits, leaves, and branchlets were poured into a separatory funnel, and then 200, 300, and 200 mL of 96% aqueous ethanol was added to each one. The mixture was macerated in the closed separatory funnel for 48 h. The outlet of the separatory funnel was opened, and the liquid was allowed to drip slowly, as specified in the method by Sabzikar et al (2020). The liquid was clarified by filtration and finally concentrated to dryness, in a Petri plate at a laboratory temperature (25 ± 5 °C) under a laminar hood to avoid chemical alteration in the bioactive compounds with loss of their properties.…”
Section: Preparation Of Extractsmentioning
confidence: 99%
“…The liquid was clarified by filtration and finally concentrated to dryness, in a Petri plate at a laboratory temperature (25 ± 5 °C) under a laminar hood to avoid chemical alteration in the bioactive compounds with loss of their properties. The extracts were accumulated and dried over anhydrous sodium sulfate and then stored at 4 ºC until further analysis (Sabzikar et al 2020). The extracts' weights from fruit, leaf, and branchlet components were 0.20, 0.25, and 0.15 g, respectively.…”
Section: Preparation Of Extractsmentioning
confidence: 99%